Pentingnya Struktur Modal Untuk Meningkatkan Kinerja Keuangan Perusahaan Sub-Sektor Teknologi - Budiarto, Dekeng Setyo; Afifah, Nur Firyal (Universitas PGRI Yogyakarta, 2024)
This research aims to determine the impact of investment decision, structure capital, and tax aggressiveness on financial performance.. This type of research is quantitative research that uses secondary data in 2018-2022 periods. The sample used was 44 technology subsector companies listed on the Indonesia Stock Exchange (BEI). This research uses purposive sampling method with certain criteria. There were 63 data obtained which were used in this research. The hypotheses in this research were analysis uses multiple linear regression. The results of this research show that 1) investment decisions have no significant effect on the company's financial performance, 2) capital structure has a positive significant effect on the company's financial performance, 3) tax aggressiveness have no significant effect on the company's financial performance